Annual Plan 1985-86 Government of India Planning Commission - Planning Commission (Planning Commission, 1985)
The Annual Plan for 1985-86, which marks the beginning of the Seventh Five Year Plan, has the distinct advantage of starting in a favourable climate. The overall target for growth rate of Gross Domestic Product (GDP) in the Sixth Plan was achieved. The success in agriculture, particularly in food production, was spectacular and so was the growth in crude oil production.
Government of India, Planning Commission